The role of the Consortia in the Italian wine production system and the impact of EU and national legislation - Carlotta Gori; Veronica Alampi Sottini (Wine Economics and Policy, 2014)
The EU legislation has undergone a radical change in 2008, handling the Italian legislature the necessity to rethink on fundamental aspects of the national legislation. The changes were focused on the procedure of formation and revision of the designations of origin, opening up new and important perspectives for Consortia since, as inter-branch organizations, they can be acknowledged as representatives of the economic activities linked to the production and at least to one of the phases of processing or trade. The Consortium has become responsible for production specification, stock managing, new registration of the vines to a DO, supervision and protection.
Keywords: 330; Consortia; EU legislation; Italian legislation; Italian production system